Microstructure, Durability and Mechanical Properties of Mortars Prepared Using Ternary Binders with Addition of Slag, Fly Ash and Limestone - Javier Ibáñez-Gosálvez; Teresa Real-Herraiz; José Marcos Ortega (Applied Sciences, 2021)
In order to improve the contribution to sustainability of cement production, several strategies have been developed, such as the incorporation of additions as clinker replacement. Regarding the production of commercial cements with additions, those made with binary binders are mostly produced. However, the use of ternary binders for manufacturing commercial cements is still very low, at least in Spain, and they could also be an adequate solution for producing eco-friendly cements. The objective of this research is to study the effects in the long term produced by ternary binders which combine the additions of blast furnace slag, fly ash and limestone in the microstructure, durability and mechanical performance of mortars, compared to mortars without additions and mortars made with binary binders. The ternary and binary binders accomplished the prescriptions for a cement type CEM II/B. The microstructure was characterized using mercury intrusion porosimetry, electrical resistivity and differential thermal analysis. Absorption after immersion, diffusion coefficient, mechanical strengths and ultrasonic pulse velocity were studied. The best performance was noted for ternary binder with both slag and fly ash, probably produced by the synergetic effects of slag hydration and fly ash pozzolanic reactions. These effects were more noticeable regarding the compressive strength.